DIPG-63. RADIATION DNA DAMAGE REPAIR INHIBITION BY GSK-J4 INDUCED CHROMATIN COMPACTION IN DIPG. Issue 2 (22nd June 2018) - Louis, Nundia; He, Xingyao; Unruh, Dustin; Piunti, Andrea; Zou, Lihua; Ozark, Patrick; Tianc, Xiao; Gorbunova, Vera; Katagi, Hiroaki; Gryzlo, Daniel; Zhang, Ali; Saratsis, Amanda; et al.
Abstract: INTRODUCTION: Focal radiation therapy remains the only treatment option for diffuse intrinsic pontine glioma (DIPG). However, all patients show evidence of disease progression within months of completing radiation therapy (RT). Since chemotherapy does not provide significant outcome improvement, it is crucial to find a suitable radiosensitizer. Our research has shown that the JMJD3 demethylase inhibitor, GSK-J4, exerts potent anti-tumor activity on DIPG cells while restoring methylation. We hypothesized that GSK-J4 may inhibit radiation-induced DNA repair, making it a potential radiosensitizer. METHODS: RNA seq was conducted to analyze gene expression changes by GSK-J4 in DIPG cells. We evaluated DNA damage repair by immunocytochemistry of DSB markers γH2AX and 53BP1 and DNA repair assay. Western blotting and quantitative PCR (qPCR) were conducted to evaluate differential expression of mRNA and proteins involved in DNA DSB repair. In vivo response to radiation monotherapy and combination of RT + GSK-J4 were measured by animal survival studies. RESULTS: RNA seq and qPCR showed that GSK-J4 significantly reduces DNA DSB repair genes in DIPG cells. Immunocytochemistry results support that GSK- J4 sustains high levels of γH2AX and 53BP1 in irradiated DIPG cells, thereby inhibiting DNA DSB repair. DNA repair assay showed that GSK-J4 inhibits DNA damage repair through the homologous recombination pathway. Western blotting revealed that GSK-J4 causes a sustained level of phosphorylated Rad50 and gH2AX in irradiated DIPG cells. In vivo studies revealed increased survival of animals treated with combination therapy compared to monotherapy. These results highlight GSK-J4 as a potential radiosensitizer in DIPG treatment.